Printed Hindi Number Recognition - Dhanoon, Ban N; Ali, Huda H (Al-Nahrain Journal of Science, 2013)
A new simple, fast, and efficient method is used in this research for recognizing Hindi numerals (0,1,2,3,4,5,6,7,8,9), that are usuallyused by Arabic population. This method is simply depends on determining number of terminal points and its positions. Only four features are added when there are similarity between numerals (have the same number of terminals and position). Different fonts with different sizes are tested and the result of the recognition rate for 13 font type is 100%.